Trust, Transgression and Surrender: Exploring Teacher and SEND Student Perceptions of Engagement with Creative Arts Project-Based Learning (CAPBL) Pedagogies - James Tarling (MDPI AG, 2023)
CAPBL is an example of a student-led, Creative Arts/Project-Based Learning (CAPBL/PBL) curriculum approach to working with Special Educational Needs and Disabilities (SEND) learners. This mixed-methods, quasi-experimental study seeks to explore staff and student perceptions of working in this way and establish key themes for practice in relation to equity and inclusion. Although the literature on PBL is widespread, CAPBL is novel in that it brings these ideas to a specialist SEND, post-16 context, Further Education (FE), with a particular focus on arts education currently absent from the existing literature. This small-scale research project is positioned as a participant-led action research project involving qualitative/quantitative mixed-method instruments, bassline testing, questionnaires, and semi-structured interviews. Preliminary findings indicate that students and staff experience several benefits to working this way, including positive engagement with learning, self-efficacy, and ownership. This paper attempts to provide workable conclusions for practice located within theoretical frameworks that offer professional resistance to prevailing preoccupations with prescription in curriculum design and pedagogy both nationally and internationally. Specifically, civic compassion and pedagogical partnership are considered in relation to the experiences of learners and staff attempting to work this way. By challenging dominant paradigms of knowledge-led learning at a national level, CAPBL seeks to actively include SEND learners in the global processes of curriculum design itself.